Facilitators and Barriers Factors of Exclusive Breastfeeding Practice among Unemployed Mothers: A Scoping Review - Dewi Epipania Naibaho; Syamsulhuda Budi Musthofa; Ratih Indraswari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Exclusive breastfeeding confers numerous health benefits on both mother and baby. Global data demonstrate that breastfeeding rates have not yet reached the 50% mark, indicating that more than half of the world's infants are not being exclusively breastfed. While unemployed mothers are known to be more likely to exclusively breastfeed, not all unemployed mothers have the ability to do so. The primary objective of this scoping review was to identify barriers and facilitators to exclusive breastfeeding among unemployed mothers. Methods: The review was conducted in accordance with the PRISMA guidelines, encompassing a systematic search of three databases (Scopus, PubMed, and EBSCOHost) for relevant articles published between 2014 and 2024. The initial search yielded 211 articles; however, only eight articles that met the predefined inclusion criteria were selected for further examination. Results: This review examined the barriers and enablers of exclusive breastfeeding among unemployed mothers by conducting a comprehensive analysis of eight articles published between 2017 and 2021. The articles under consideration were derived from a total of 211 articles collected across three databases using specific keywords and filtering tools. The classification of factors was conducted in accordance with L. Green's framework, which categorizes factors as predisposing, reinforcing, and enabling. The facilitator factors that were identified included adequate antenatal care, prior breastfeeding experience, and strong knowledge. The identified barriers encompassed caesarean delivery, health concerns, and inadequate knowledge. The practice of breastfeeding was influenced by a variety of factors, including family dynamics, healthcare support systems, and cultural norms. Conclusion: The findings from this review indicate the presence of predisposing and enabling factors in the internal aspects of the mother, infant condition, culture, support, health services, and other health practices. Predisposing factors play an important role as both enablers and barriers to exclusive breastfeeding in non-working mothers. This review highlights the need for more comprehensive interventions to assist mothers in improving exclusive breastfeeding practices.